Antisemitismus, Antizionismus und Ausnahmen: positive Bezüge auf Israel und Zionismus von rechts in historischer Perspektive - Schreiter, Nikolai (Aschkenas, 2022)
This article analyzes the turn towards Israel in parts of the German and Austrian extreme right since 2010 in a historical perspective. Both political parties in the focus of the analysis, AfD and FPÖ, and the extreme right in general have a history of antisemitism, antizionism and hostility towards Israel and Zionism. After establishing antizionism as an inherent part of antisemitism almost from its outset, several exceptions from this rule are analyzed with respect to the relationship of the two. All of the introduced positive references towards Zionism and Israel from an antisemitic background will turn out to be based on antisemitic images of Jews, Zionism and the State of Israel. They fulfill a certain end to antisemitism itself, its denial and its bearers, and thus serve the preservation of the ideology rather than, as has been suggested, marking an end to antisemitism or being solely strategically motivated.